Isolated Chronic Exertional Compartment Syndrome of the Lateral Lower Leg: A Case Series. Issue 11 (23rd November 2015) - van Zantvoort, Aniek P.M.; de Bruijn, Johan A.; Winkes, Michiel B.; Dielemans, Jeanne P.; van der Cruijsen-Raaijmakers, Marike; Hoogeveen, Adwin R.; Scheltinga, Marc R.
Background: Exercise-induced lower leg pain may be caused by chronic exertional compartment syndrome (CECS). The anterior (ant-CECS) or deep posterior compartment (dp-CECS) is usually affected. Knowledge regarding CECS of the lateral compartment (lat-CECS) is limited. Purpose: To describe demographic characteristics and symptoms in a consecutive series of patients with isolated CECS of the lateral compartment of the leg. Study Design: Case series; Level of evidence, 4. Methods: Since 2001, patients undergoing dynamic intracompartmental pressure (ICP) measurements for suspected CECS in a single institution were prospectively monitored. Individuals with a history possibly associated with lat-CECS and elevated ICP measurements (Pedowitz criteria) were identified. Exclusion criteria were concomitant ipsilateral ant-CECS/dp-CECS, acute compartment syndrome, recent significant trauma, peroneal nerve entrapment, or vascular claudication. Results: During an 11-year time period, a total of 26 patients with isolated lat-CECS fulfilled study criteria (15 females; median age, 21 years; range, 14-48 years). Frequently identified provocative sports were running (n = 4), walking (n = 4), field hockey (n = 3), soccer (n = 3), and volleyball (n = 2). Exercise-induced lateral lower leg pain (92%) and tightness (42%) were often reported. The syndrome was bilateral in almost two-thirds (62%, n = 16). Delay in diagnosis averaged 24 months (range, 2 months to 10 years). Conclusion: Young patients with exercise-induced pain in the lateral portions of the lower leg may suffer from isolated CECS of the lateral compartment. ICP measurements in the lateral compartment in these patients are recommended.